Comparative Analysis of the Performance of Cryptocurrency Bitcoin, Sharia Stocks, and Gold as Investment Alternative - Riniawati , Riniawati; Fatoni, Ahmad; Badina, Tenny (Goodwood Publishing, 2025)
Purpose: This study aims to analyze and compare the performance of Bitcoin, JII (Jakarta Islamic Index) stocks, and ANTAM gold as investment alternatives from 2019 to 2023. Methodology/approach: A quantitative approach with a comparative method was used, utilizing secondary time series data. Monthly closing prices of Bitcoin, JII stocks, and ANTAM gold from 2019-2023 were analyzed. The study used saturated sampling with 180 data points. Parametric (One-Way ANOVA) and non-parametric (Kruskal-Wallis) tests were applied, depending on data normality and homogeneity. Results/findings: The study found no significant difference in returns between Bitcoin, JII stocks, and ANTAM gold (p = 0.412 > 0.05). However, a significant difference was observed in risk levels (p = 0.00 < 0.05), with Bitcoin being the riskiest. Performance analysis via the Sharpe and Treynor indices showed Bitcoin as the best-performing instrument, followed by gold and JII stocks. The Jensen index revealed no significant difference in performance, with JII stocks slightly outperforming the others. Conclusions: Bitcoin offers the highest return but carries the highest risk. JII stocks and gold show lower risk but also lower returns. Bitcoin outperforms other instruments in performance based on Sharpe and Treynor indices, while JII stocks are slightly better when using the Jensen index. Limitations: The study focused only on JII-listed Islamic stocks, and data were limited to the 2019-2023 period. Contribution: This research provides insights for investors, particularly Muslim investors, on the comparative performance of these investment options.